From Gunmen to Politicians:: The Impact of Terrorism and Political Violence on Twentieth-Century Ireland - White, Robert (Journal of Conflict Studies, 2007)
Abstract Many terrorist groups, it would seem, cause great turmoil but no lasting impact. This might include radical student groups of the 1960s and terrorist organizations of the 1970s. Yet, we know that in some instances political violence, or revolution, does lead to great social change. Consider Cuba as an example. This might suggest that terrorists and revolutionaries face a zero-sum game: total failure or total victory. There is a middle ground, however. The PLO, as an example, has not achieved an independent Palestine, but who in the 1970s would have imagined a Palestinian Authority led by Yasir Arafat. This case study of the Irish Republican Army and its political wing, Sinn Fein, examines this middle ground in Ireland in the 1916-1948 time period.